PENGARUH KUALITAS PENGUNGKAPAN INFORMASI TERHADAP HUBUNGAN ANTARA CORPORATE GOVERNANCE DENGAN KINERJA PERUSAHAAN - Indahsari, Putri Ayu Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to measure the influence of information disclosure quality to the relation between the implementation of corporate governance and company performance. The implementation of corporate governance uses the research result indicator from The Indonesian Institute for Corporate Governance. The company performance uses two indicators which are operational performance through return on equity (ROE) and market performance through Tobinâs Q. The information disclosure quality is assessed from the mandatory disclosure which is measured by using Wallace index. The selection of samples are performed by using purposive sampling method. The total amount of samples are as many as 77 observations from 2008-2011. The analysis instruments which are applied in this research are the multiple regression analysis and moderated regression analysis (interaction test). The result of research shows that the implementation of corporate governance, information disclosure quality, and company size simultaneously have an influence to the company performance either through ROE or Tobinâs Q. While partially the implementation of corporate governance has an influence to the market performance, but it has no influence to the operational performance. Partially the information disclosure quality has no influence to the operational performance and market performance. While partially the size of the company has an influence to the operational performance but it has no influence to the market performance. Meanwhile, the information disclosure quality influence the relationship between the implementation of corporate governance and the operational performance, but it has no influence the relationship between the implementation of corporate governance and market performance.Keywords: Corporate Governance, Mandatory Disclosure, Company Performance